Usefulness and outcome of whole-body computed tomography (pan-scan) in trauma patients: A prospective study - Harntaweesup S. (2023)
Background: Severe trauma can cause multi-organ injuries, and the mortality rate may increase if significant organ injuries are missed. This study was performed to determine whether whole-body computed tomography scan (pan-scan) can detect significant injury and leads to proper management, including alteration the priority of management. Methods: This prospective study was conducted from January 2019 to March 2021 and involved trauma patients level 1, level 2, and dangerous mechanism of trauma. Additionally, the data of trauma patients who had selective computed tomography scan were retrospectively reviewed to compared the clinical benefits. Results: Twenty-two patients were enrolled in the prospective study. The pan-scan detected significant organ injury in 86% of the patients. Prioritization of organ injury management changed after performance of the pan-scan in 64% (major change in 64.29% and minor change in 35.71%). Skull base fracture, small bowel injury, retroperitoneal injury, kidney and bladder injury, and occult pneumothorax were the majority of injuries which was not consider before underwent pan-scan (p < 0.05). The door-to-scan time tended to be shorter in the pan-scan group than in the selective scan group without a significant difference [mean (SD), 59.5 (34) and 72.0 (86) min, respectively; p = 0.13]. Pan-scan contribute 100% confidence for trauma surgeon in diagnosis of specific organ injuries in severe injured patients. Conclusions: The pan-scan facilitates timely detection of significant unexpected organ injuries such as the skull base, occult pneumothorax, small bowel, and retroperitoneum. It also helps to prioritize management and increases the diagnostic confidence of trauma surgeons, leading to better outcomes without delay.